Sustainable Housing 2022
DOI: 10.5772/intechopen.99263
|View full text |Cite
|
Sign up to set email alerts
|

Housing Challenges in Nigeria

Abstract: One of the policy goals of sustainable development is the delivery of adequate housing for Countries in the global south. This is because in many countries of the global south housing is delivered more through private mechanisms, consequently this poses challenges to adequate housing delivery for most countries of the global south and the Nigeria populace. Some of the challenges faced in providing decent and adequate housing for the people include problems of unskilled workmen, unachievable westernized buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Researchers have identified housing delivery problems in developing countries, including Nigeria, and proposed guiding principles for successful housing delivery (Mukhtar, Amirudin, & Mohamad, 2016, Ezeanah, 2018, Ezeanah, 2021b. However, we still need to fully address the application of these principles in Jos and their alignment with the city's specific needs and constraints.…”
Section: Wwwafropolitanjournalscommentioning
confidence: 99%
“…Researchers have identified housing delivery problems in developing countries, including Nigeria, and proposed guiding principles for successful housing delivery (Mukhtar, Amirudin, & Mohamad, 2016, Ezeanah, 2018, Ezeanah, 2021b. However, we still need to fully address the application of these principles in Jos and their alignment with the city's specific needs and constraints.…”
Section: Wwwafropolitanjournalscommentioning
confidence: 99%
“…All of these oddities, however, may be remedied through affordable housing standards. A fundamental institutional approach for affordable dwellings is centred on an efficient and clear procurement procedure [47]. Favouritism, ineptitude, and excessive thirst for profits may all be handled with an open and successful procurement procedure.…”
Section: Institutional Approaches To Affordable Housingmentioning
confidence: 99%
“…The environment, product quality, price, and on-time delivery of goods will become more demanding, and tax and innovation measures can assist (Ezeanah, 2021). Due to a shortage of capital, rising building costs, and a decrease in customers expecting more from their services, developers are now operating in unfamiliar terrain after leading the real estate business for decades.…”
Section: Purchasing Powermentioning
confidence: 99%
“…The product throughout the real estate, unlike some other markets, entails a "change of land use" or an "alteration to an existing building" in addition to other productive resources, including the labor (Gambo, 2019); materials (Jiburum et al 2021); and financial services (Arudi et al 2022). 2 Ezeanah (2021) and Ezennia (2022), in their previous research, "identified an increase in construction costs, high cost of capital, the availability of land, sharp amortization of the Naira, access to mortgage lending facilities, amount of production, poor infrastructural requirement, extortion by federal officers, costs for building materials, and governmental policies," are cited by (Maiyaki et al 2021) as saying that property or development of residential properties in Nigeria has recently faced many challenges.…”
Section: Introductionmentioning
confidence: 99%